2001
DOI: 10.1128/jb.183.7.2359-2366.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas stutzeri Has Two Closely Related pilA Genes (Type IV Pilus Structural Protein) with Opposite Influences on Natural Genetic Transformation

Abstract: Pseudomonas stutzeri has type IV pili for which the pilA gene (here termed pilAI) provides the structural protein and which are required for DNA uptake and natural genetic transformation. Downstream of pilAI we identified a gene, termed pilAII, coding for a deduced protein with a size similar to that of PilAI with 55% amino acid sequence identity and with a typical leader peptide including a leader peptidase cleavage site. Fusions to lacZ revealed that pilAII is expressed only about 10% compared to pilAI, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Mutation of pilAI abolished piliation, while a pilAII mutant expressed surface pili and had increased transformability (159). Interestingly, the hypertransformation phenotype was maintained in a P. stutzeri pilAI pilAII double mutant expressing pilins from nonnaturally transformable species such as P. aeruginosa (159).…”
Section: Tandem Chromosomal Pilin Locimentioning
confidence: 93%
“…Mutation of pilAI abolished piliation, while a pilAII mutant expressed surface pili and had increased transformability (159). Interestingly, the hypertransformation phenotype was maintained in a P. stutzeri pilAI pilAII double mutant expressing pilins from nonnaturally transformable species such as P. aeruginosa (159).…”
Section: Tandem Chromosomal Pilin Locimentioning
confidence: 93%
“…They are probably located in the cytoplasm and in the inner membrane, respectively (125 (56,71,210,262,403). Surprisingly, the genetic inactivation of P. stutzeri pilAII produced a hypertransformation phenotype (127). It has been suggested that the role of PilAII is to interfere with DNA transport within the cell following DNA uptake.…”
Section: Natural Transformationmentioning
confidence: 99%
“…Although much information has been obtained for Bacillus subtilis and Neisseria gonorrhoeae-see a review by Chen and Dubnau (67)-the transformation machinery of P. stutzeri has been studied only recently (125)(126)(127)(128)220). It has been demonstrated that P. stutzeri naturally transforms both duplex and single-stranded DNA using the same machinery.…”
Section: Natural Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotype of enhanced competence, termed hypercompetence, has been described previously for bacterial mutants with defects in regulatory factors that increase or deregulate expression of the competence regulon (24,28,33,49,53). Hypercompetence can also result from mutations in components of the uptake machinery, as seen in P. stutzeri (18). Finally, hypercompetence can be induced indirectly: for example, an H. influenzae mutant with an altered peptidoglycan biosynthesis gene causes induction of the normal competence pathway (32).…”
mentioning
confidence: 99%